Soft sediment deformation structures and their implications for Late Quaternary seismicity on the South Tibetan Detachment System, Central Himalaya (Uttarakhand), India - Naresh, Rana; Bhattacharya, Falguni; Basavaiah, N.; Pant, R.K.; Juyal, Navin (My University, 2013)
The South Tibetan Detachment System (STDS) defines the lithological and tectonic boundary between the Higher Himalayan crystallines and the Tethyan sedimentaries. Earlier studies have suggested that the STDS has been dormant since its inception during the Miocene along with the Main Central Thrust (MCT). However, recent studies indicate that the STDS was active during the Pleistocene–Holocene period. We provide additional support for this more recent activity based on the occurrence of seismically induced Soft Sediment Deformation Structures (SSDS) preserved in relict lake sediments in the Dhauli Ganga, Gori Ganga and Kali Ganga river basins of the Central Himalaya. The relict lakes are located on the hanging wall of the STDS. An optical chronology of the lake sediments brackets the seismically induced SSDS between 20 ka and 11 ka with a major seismic event of magnitude > 6.5 occurring between 17 ka and 13.5 ka. Since MCT and STDS are considered to be the coupled structures, our observation supports the hypothesis that the STDS is providing accommodation space to the strain gradient arising due to the north–south compression in the Himalaya during the late Quaternary.
Keywords: Soft sediment deformation; STDS; Seismicity; Tethys Himalaya; Late Quaternary; South Tibetan Detachment System